Popular university in brazil and ethnic-racial relations: the case of the University of International Integration of Afro-brazilian Lusophony (UNILAB) - Silva, Maurício (Universidade Estadual de Campinas, 2018)
This article analyzes how to set up, in contemporary Brazil, popular universities - a category we will seek to define here - and how to fall in this category, ethnic and racial issues, especially related to the higher education process. To illustrate this relationship between popular university and ethnic and racial issues, this article analyzes the case of the Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), verifying specific aspects of this university, in correlation with the above categories.